PENGARUH MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR TIK DI TINJAU DARI MOTIVASI BERPRESTASI PADA SISWA KELAS X SMA MUHAMMADIYAH PANGKAJENE - Nur Husna; Haerul Syam; Ratnawati; Alianas Alianas (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study was to determine the application of the Inquiry learning model to improve ICT learning outcomes with achievement motivation covariables in class X students at SMA Muhammadiyah Pangkajene in the 2022/2023 academic year. This research is classified as a non-equivalent control group design, with the research subjects being 14 students of class X Social Sciences SMA Muhammadiyah Pangkajene. The instrument used is a test consisting of 5 questions. The results of observations in the first cycle of learning outcomes by applying the Inquiry learning model obtained learning completeness reached 68% or 8 students out of 14 students had completed learning. The results of observations in the second cycle of complete learning outcomes reached 76% or 11 students out of 14 students had completed learning. From the results of the actions in the first cycle and in the second cycle, it is concluded that the application of the Inquiry learning model can improve ICT learning outcomes with the achievement motivation covariable of class X students at SMA Muhammadiyah Pangkajene for the academic year 2022/2023.